BENTUK DAN FAKTOR PENERAPAN DIGITALISASI PELAYANAN PUBLIK OLEH PEMERINTAH - Yafie, Azmi Ali; Santosa, Imam; Masrukin (UNIVERSITAS STEKOM, 2025)
Digitalization of public services is being implemented across Indonesian government agencies, including village governments. This study aims to describe the forms of public service digitization and the factors influencing its implementation in village governments. Using a qualitative literature study method, secondary data from research journal articles were analyzed through data selection, organization, interpretation, and conclusion. The findings reveal that village government digitization involves websites and applications. Key influencing factors include E-Government implementation, conventional management, disorganized administration, service improvement, government policies, and the Covid-19 pandemic.